Seasonal incidence of apple leaf miner (Lyonetia clerkella (L., 1758), Lepidoptera, Lyonetiidae) in Kashmir, India - Sumiulah RATHER; Abdul A. BUHROO; Abdul Lateef KHANDAY (Acta Agriculturae Slovenica)
The seasonal incidence of apple leaf miner (Lyonetia clerkella [L., 1758], Lepidoptera, Lyonetiidae) was investigated in four districts of Kashmir valley from March 2015 to April 2016. The prevalence of infestation was found higher in Srinagar (70.6 %) and Bandipora (65.3 %) as compared to Pulwama (9.3 %) and Baramulla (6.6 %). Infestation  intensity was  found  at  its  peak  during  the  month of May (2015) in all the four districts. In Srinagar, the percent infestation intensity during May (2015) was found to be 58.69 % (± 11.46 SD), while as in Bandipora, Pulwama and Baramulla, it was found as 55.71 % (± 12.59 SD), 6.04 % (± 1.97 SD) and 4.27 % (± 1.12 SD) respectively. Infestation of intensity was observed to decline linearly from the first week of June (2015) and disappeared completely with the beginning of winter season. Further, seven generations of L. clerkella were found under laboratory conditions. The1st, 2nd, 3rd, 4th, 5th, and 6th generations completed in 39, 40, 37, 39, 45 and 48 days respectively. However, final generation (7th) was found relatively longer in duration, extended from the 4th week of September (2015) till April of the following year (2016) for about 204 days. In general, the life cycle of L. clerkella is similar to those described for other leaf miner species.